1982
DOI: 10.1128/iai.37.2.407-412.1982
|View full text |Cite
|
Sign up to set email alerts
|

Experimental infection and immune response of guinea pigs with varicella-zoster virus

Abstract: An immune response (fluorescent antibody to membrane antigen) was detected in guinea pigs inoculated with varicella-zoster virus (VZV) adapted to guinea pig embryonic cells, including the Oka vaccine strain, even when inoculation was by an external route, i.e., nasal or corneal. Live or UV-inactivated virus having the same virus titer before irradiation was administered to guinea pigs by the corneal route, and antibody induction was detected only with live virus. The transmission of VZV from infected guinea pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

1984
1984
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(20 citation statements)
references
References 10 publications
0
20
0
Order By: Relevance
“…Antibody responses to VZV were also observed in guinea pigs. In this species antibody titers were found only after inoculation of the attenuated OKA strain but not after inoculation of the nonattenuated OKA or other wild VZV strains [Matsumaga et al, 1982;Yamanishi et al, 19801. It is likely that the immunogenicity of the attenuated OKA strain in guinea pigs was due to the series of passages in embryonic guinea pig cell cultures performed in the course of attenuation [Takahashi et al, 19751. The findings taken in their sum suggest that subhuman primates and other animal species have the capability of responding in a particular way to strains of VZV which have an altered pathogenicity for humans.…”
Section: Discussionmentioning
confidence: 99%
“…Antibody responses to VZV were also observed in guinea pigs. In this species antibody titers were found only after inoculation of the attenuated OKA strain but not after inoculation of the nonattenuated OKA or other wild VZV strains [Matsumaga et al, 1982;Yamanishi et al, 19801. It is likely that the immunogenicity of the attenuated OKA strain in guinea pigs was due to the series of passages in embryonic guinea pig cell cultures performed in the course of attenuation [Takahashi et al, 19751. The findings taken in their sum suggest that subhuman primates and other animal species have the capability of responding in a particular way to strains of VZV which have an altered pathogenicity for humans.…”
Section: Discussionmentioning
confidence: 99%
“…Research on the consequences of VZV infection in neurons has been hampered by the lack of a suitable animal model. Investigators have had limited success in infecting guinea pig DRG (Arvin et al 1987;Lowry et al 1992Lowry et al , 1993Matsunga et al 1982;Myers et al 1980Myers et al , 1985Myers et al , 1991Sato et al 2003) and, although latent infection of ganglia has been achieved in cotton rats (Cohen et al 2007) and rats (Rentier et al 1996), VZV has not been reactivated in either of these animals. We have furthered our own ability to analyze the life cycle of VZV by developing an in vitro model that utilizes enteric neurons isolated from the guinea pig small intestine (Chen et al 2003;Gershon et al 2008b).…”
Section: Introductionmentioning
confidence: 99%
“…We, therefore, sought to develop a guinea pig model, which would be accessible and relevant to infection and latency of VZV in neurons. Guinea pigs were chosen as the animals to study because of the prior limited success other investigators have had in infecting guinea pig cells [Myers et al, 1980[Myers et al, , 1985Matsunga et al, 1982;Arvin et al, 1987;Lowry et al, 1992Lowry et al, , 1993Sabella et al, 1993;Cohen et al, 1998;Sato et al, 1998] moreover, the Oka strain of VZV, which is used in the varicella vaccine, was adapted for this purpose by multiple passages in guinea pig fibroblasts [Takahashi et al, 1974;Matsunga et al, 1982;Lowry et al, 1992Lowry et al, , 1993. These observations suggested that guinea pig neurons might be infected with VZV more readily than those from other species.…”
Section: Introductionmentioning
confidence: 99%